Utilization of Trichoderma harzianum SNRS3 for sugar recovery from rice straw for acetone-butanol-ethanol production by Clostridium acetobutylicum ATCC 824 - Rahnama, Nooshin (2013)
Acetone-Butanol-Ethanol ﴾ABE﴿ production from various agricultural residues has been a recent issue of interest for many scientists. However, research carried out on ABE production from rice straw is limited. Pretreatment and hydrolysis required prior to fermentation are costly. Hence, the aims of the study were to produce cellulolytic enzyme complex ﴾FPase, CMCase, and β-glucosidase﴿, and xylanolytic enzyme ﴾xylanase﴿ from untreated rice straw by local Trichoderma harzianum SNRS3 and to utilize the crude cellulolytic enzyme complex for sugar production through enzymatic hydrolysis of alkali-pretreated rice straw which was finally used as the substrate for ABE production. The use of untreated rice straw as the substrate for enzyme production by T. harzianum SNRS3 under solid state fermentation resulted in the production of cellulase and xylanase at a higher activity (FPase 6.25 U/g substrate, CMCase 111.31 U/g substrate, β-glucosidase 173.71 U/g substrate, and xylanase 433.75 U/g substrate), as compared to when alkali-pretreated rice straw was used as fermentation substrate (FPase 1.72 U/g substrate, CMCase 23.01 U/g substrate, β-glucosidase 2.18 U/g substrate, and xylanase 45.46 U/g substrate). The results of XRD analysis indicated an increase in relative crystallinity of cellulose due to the hydrolyzation and peeling of amorphous regions during pretreatment. The SEM images showed that the pretreatment process disrupted the hemicelluloses and lignin, which might have caused the changes in the structure of cellulose. According to the results of FTIR analysis, alkali pretreatment caused lignin removal and the changes in the structure of cellulose. In fact, alkali pretreatment of the substrate caused the crystallinity of cellulose to decrease. Absolute crystallinity could most impact cellulase production. However, the overall complexity of the untreated substrate might have actually induced greater enzyme production. The crude cellulase enzyme produced by T. harzianum SNRS3 via solid state fermentation was then characterized. At 60 ºC, β-glucosidase activity was still above 70% of its maximum activity and FPase and CMCase remained active almost up to 100% that could be an advantage for cellulases. FPase and CMCase retained their highest activity in the acidic region over an almost broad pH range that is considered an advantage for industrial enzymes. At room temperature, FPase almost retained 60% of its original activity at the end of week 3 of storage. Whereas, CMCase retained 60% of its original activity at the end of the 2nd week of storage at room temperature. β-glucosidase activity only decreased to above 80% of its original activity at the end of the 3rd week of storage at room temperature. Saccharification of alkali-pretreated rice straw was conducted to obtain reducing sugar for use as fermentation substrate. The use of rice straw pretreated with 2% (w/v) NaOH resulted in the production of 5.82 g/L reducing sugar after 72 h of enzymatic hydrolysis. At 5% (w/v) substrate, a reducing sugar yield of 0.6 g/g substrate was obtained that was equivalent to 60.75% saccharification. Rice straw hydrolysate containing 10 g/L glucose was then utilized as the substrate for ABE production by Clostridium acetobutylicum ATCC 824. Rice straw was shown to be a potential substrate for ABE production and a maximum total ABE of 2.73 g/L (0.82 g/L acetone, 1.62 g/L butanol, and 0.29 g/L ethanol) at 72 h was obtained. Fermentation of rice straw hydrolysate resulted in an ABE yield of 0.27 g/ g glucose. Therefore, untreated rice straw serves as a better substrate than alkali-pretreated rice straw for cellulase production and produced a higher cellulase enzyme activity for the subsequent use in saccharification for production of glucose which finally can be utilized as the substrate for ABE production. The results of this study could contribute to future research on production of cellulolytic enzymes from lignocellulosic agricultural waste including rice straw for their various industrial applications such as their use in biomass-biofuel conversion.